Medicaid trends in prescription opioid and non-opioid use by HIV status. (1st April 2019) - Canan, Chelsea; Alexander, G. Caleb; Moore, Richard; Murimi, Irene; Chander, Geetanjali; Lau, Bryan
Highlights: Prescription opioid and non-opioid analgesics increased dramatically from 2001 to 2009. People living with HIV receive more prescription analgesics than those without HIV. Chronic opioid therapy is common among people living with HIV. Demographic and clinical factors largely explain the differential prescribing rates. Abstract: Background: Pain is more common among people living with HIV (PLWH) than their counterparts; however, it is unclear whether analgesic use differs by HIV status. Methods: We analyzed Medicaid pharmacy claims from adults in 14 US states from 2001 to 2009 to identify opioid and non-opioid analgesic prescriptions and compared prescribing trends by HIV status. We accounted for clinical and demographic differences by using inverse probability weights and by restricting the sample to a subgroup with a common comorbidity, diabetes, chosen for its high prevalence and association with lifestyle and chronic pain. We estimated the incidence of chronic opioid therapy (COT) (≥90 consecutive days with an opioid prescription) among opioid-naïve individuals. Results: Rates of opioid and non-opioid use increased approximately two-fold from 2001 to 2009. PLWH received approximately twice as many prescriptions as those without HIV. In an unadjusted Cox regression, PLWH were three times more likely to receive COT compared to those without HIV (hazard ratio (HR) = 3.06, 95% CI 2.76–3.39). When restricting to patients with diabetes and adjusting for age, sex, state, comorbidity score, depression, bipolar disorder, and schizophrenia, the HR decreased to 1.26 (95% CI 0.97–1.63). Conclusions: Higher opioid use among PLWH was largely a function of patients' demographic characteristics and health status. The high incidence of COT among PLWH underscores the importance of practice guidelines that minimize adverse events associated with opioid use.